Parental Overcontrol and Adolescent Risk-Taking: The Mediating Role of Peer Conformity - Sari, Intan; Deshmukh, Arjun; Nishimura, Haruka (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the relationship between parental overcontrol and adolescent risk-taking, with peer conformity as a potential mediating variable. Methods and Materials: A descriptive correlational design was used, involving 449 adolescents aged 15–18 from secondary schools in India. Participants were selected using stratified random sampling, based on the Morgan and Krejcie sample size table. Standardized instruments were used to measure parental overcontrol, peer conformity, and adolescent risk-taking. Data analysis was conducted using SPSS version 27 for descriptive statistics and Pearson correlation, and AMOS version 21 for Structural Equation Modeling (SEM) to assess the mediating effect of peer conformity. Findings: Pearson correlation coefficients revealed significant positive relationships between parental overcontrol and peer conformity (r = .42, p < .001), parental overcontrol and adolescent risk-taking (r = .37, p < .001), and peer conformity and adolescent risk-taking (r = .49, p < .001). The SEM demonstrated a good model fit (χ²/df = 2.15, GFI = 0.95, CFI = 0.96, RMSEA = 0.051). Path analysis indicated that parental overcontrol had a significant direct effect on peer conformity (β = 0.42, p < .001) and adolescent risk-taking (β = 0.27, p < .001). Peer conformity significantly predicted adolescent risk-taking (β = 0.49, p < .001) and mediated the indirect effect of parental overcontrol on risk-taking (β = 0.21, p < .001), resulting in a total effect of β = 0.48. Conclusion: The results confirm that peer conformity partially mediates the relationship between parental overcontrol and adolescent risk-taking. Adolescents experiencing high parental overcontrol are more likely to conform to peers, increasing their vulnerability to risky behaviors. These findings highlight the need for parenting interventions that support autonomy while also addressing peer influence dynamics during adolescence.